CARGA TRIBUTÁRIA DE EMPRESAS FLORESTAIS PRODUTORAS DE MADEIRA DE Pinus spp.: UM ESTUDO DE CASO - BARGAS, LEANDRO DA SILVA (2012)
The level of taxation for business and legal person in Brazil is positioned at a high level, reaching derails certain businesses. The difficulty of measuring the tax and its effect on the profitability of forestry enterprise cannot do that thorough examination and thus devise a plan to tax, to reduce the incidence of taxes (taxes and contributions) in favor the higher profitability of the enterprise. The objective of this research was to outline a profile of the taxes levied on the production cycle and the billing of commercial plantations of Pinus spp., and even point out which tax regime the company should choose, with a focus on reducing taxes and therefore, maximize their competitiveness in the sector. By structuring a cash flow, reached to the impact of taxes on the cost of training pine forest until the 21th year, which represented 8.6% of total cost, while not considered a tax billing. In the presumed profit system, this percentage increased to 18.4%, reaching 36.6% under the taxable income. When analyzing the Net Present Values (NPV) in different tax regimes, we obtained the value of R$2.625/ha (without taxation revenue), R$ 1.331/ha (presumed profit) and negative value for the real profit regime, not reaching the Minimum Rate Attractiveness established at 8.7% per year. It was also possible to determine the economic rotation indicated that the period of clearcutting to 21 years. In present value terms, to produce a cubic meter of pine wood, there was an investment of R$ 73.22, considering taxation on billings under taxable income, whereas 46% of the composition of this cost equals taxes. The average production cost of wood, without regard to taxation on revenue was R$ 50.79/ m³. In the scenario we considered the taxation regime on presumed income, the average production cost came to R$ 56.83/ m³, and of this total, 31% correspond to taxes.